Dark of the moon ebook - Sandford, John (Virgil Flowers, 2007)
The first Virgil Flowers novel from #1 New York Times bestselling author John Sandford. “Virgil Flowers, introduced in bestseller Sandford’s Prey series, gets a chance to shine...The thrice-divorced, affable member of the Minnesota Bureau of Criminal Apprehension (BCA), who reports to Prey series hero Lucas Davenport, operates pretty much on his own..”* He’s been doing the hard stuff for three years, but he’s never seen anything like this. In the small rural town of Bluestem, an old man is bound in his basement, doused with gasoline and set on fire. Three weeks before, a doctor and his wife were murdered. Three homicides in Bluestem in just as many weeks is unheard of. It’s also no coincidence. And it’s far from over...